KEPUASAN PENGUNJUNG TERHADAP KUALITAS MAKANAN LENDOT DI KAWASAN WISATA TAMAN KOTA COASTAL AREA KABUPATEN KARIMUN - Hanisah "; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The satisfaction is compatibility of product accepted and expectation of product. The research was conducted to determine the satisfaction of visitors to the quality of food lendot in The Tourist Area Of The City Park Coastal Area Karimun Regency. The research method used is quantitative approach. The sample technique used is accidental sampling. Samples taken as many as 40 respondents who consume a lendot in the Kawasan Wisata Taman Kota Coastal Area Kabupaten Karimun, where taken into the research respondents are visitors who have never consume lendot with the intention to know expectations and performence after consume lendot. The data were collected using questionnaire, interview and observation. Analysis of data use is done by comparing expectations and performance of the responses of respondents. The results of the research indicate the performance is higher than the expectation level so that overall visitors are satisfied with the quality of food lendot in The Tourist Area Of The City Park Coastal Area Karimun Regency.Keywords: Satisfaction, Food Quality, Coastal Area